AB0390 Suicidal ideation in patients with systemic lupus erythematosus: prevalence and risk factors. (23rd January 2014) - Mok, C. C.; Chan, K. K.; Cheung, E.; Yip, P.
Abstract : Objectives: To study the prevalence of suicidal ideation in patients with SLE and its associated risk factors Methods: Consecutive patients who fulfilled 3 4 ACR criteria for SLE were recruited for a questionnaire study on suicidal ideation. Suicidal idea was assessed by: (1) Three standard questions on suicidal thoughts and suicidal plans in the past 1 month; and (2) The validated Chinese version of the Beck Scale for Suicidal Ideation (BSSI). The BSSI is a questionnaire with 19 questions that assess suicidal intention. Each question scores 0-2 and the final score is the summation of the scores of these 19 questions (0-38 points) (higher the score, greater is the suicidal intention). History of suicidal attempts and self assessment of suicidal tendency was also included as 2 other questions in this tool. Anxiety and depressive symptoms were assessed simultaneously by the Hospital Anxiety and Depression (HAD) scale (0-21 points for each of depression and anxiety). Disease activity of SLE was assessed by SLEDAI and physicians' global assessment (PGA), whereas organ damage since SLE diagnosis was assessed by the ACR SLICC damage index (SDI). The BSSI score was correlated with the basic demographic and clinical features of the participants, HAD, SLEDAI and SDI score. Linear regression models were established to study the independent factors associated with suicidal intention. Results: 381 SLE patients were studied (95% women; mean age 40.1±12.9 years; disease duration 9.2±7.1 years) - 78(20.4%) patients had clinically active SLE (SLEDAI score of >=5). 144 (38%) patients had organ damage (SDI >=1). 44(12%) patients had suicidal thoughts and 5 (1.3%) patients had suicidal thoughts together with solid plans in the preceding 1 month. 46(12%) patients had previous suicidal thoughts whereas 22(6%) had documented suicidal attempts. The mean BSSI score was 1.49±3.8 points (range 0-24; median=0; IQR=1). Compared to those without suicidal thoughts within 1 month of study, patients with suicidal thoughts on direct questioning had significantly higher BSSI scores (5.5±5.6 vs 1.0±3.1 points; p<0.001), HAD-anxiety (12.2±4.9 vs 5.6±4.1; p<0.001), HAD-depression (11.2±4.7 vs 4.4±3.8; p<0.001) scores and SDI damage score (1.4±1.7 vs 0.6±1.1; p=0.007). The BSSI score (intensity of suicidal intention) correlated significantly with HAD-depression (r 0.45; p<0.001), HAD-anxiety (r 0.44; p<0.001), male sex (r 0.12; p=0.03), total SDI score (r 0.14; p=0.007), mean SLEDAI score in the preceding 12 months (r 0.15; p=0.005), past history of psychiatric disorders (r 0.14, p=0.009), major life events in the preceding month (r 0.14; p=0.06) unemployment (r 0.19; p<0.001) and the need for financial assistance from government (r 0.12; p=0.03). In a stepwise linear regression model (R 2 =0.27), HAD-depression score (Beta 0.29; p<0.001), HAD-anxiety score (Beta 0.15; p=0.047), age (Beta 0.13; p=0.04) and total SDI score (Beta 0.10; p=0.04) and major life events (Beta 0.14; p=0.004) was significantly associated with the BSSI score. Conclusions: In this cross-sectional study, suicidal ideation in the preceding month occurs in 12% of patients with SLE. The intention of suicidal ideation is stronger in older patients, those with more end organ damage, anxiety or depressive symptoms, and major life events in the preceding month. Disclosure of Interest: None Declared